APPROACHES TO A TIPOLOGIZATION OF MIGRATORY STREAMS IN THE RUSSIAN FEDERATION - Nikita D. Epstein; Elena A Egorova; Pavel A. Smelov (Статистика и экономика)
In article investigated regional differentiation of migratory streams in Russia.The system of indicators characterizinga condition of population shift, coveringparameters of social and economic wellbeing of regions created.